Anestesi Inhalasi dengan Teknik Low Fresh Gas Flow - Pratomo, Bhirowo Yudo; Kurniawaty, Juni; Kusuma, Danur Adi (Jurnal Komplikasi Anestesi, 2022)
Any technique that employs a fresh gas flow that is less than the alveolarventilation can be classified as low-flow anesthesia. The complexities involvedin the calculation of uptake of anesthetic agents during the closed-circuitanesthesia made this technique less popular. However, the awareness of thedangers of operating theatre pollution with trace amounts of the anestheticagents and the prohibitively high cost of the new inhalational agents, havehelped in the rediscovery of low-flow anesthesia.